PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPOSIBILITY DAN CURRENT RATIO TERHADAP EARNING RESPONSE COEFFICIENT PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Khairutdin Sembiring; Heny Triastuti Kurnianingsih; Lusi Elviani Rangkuti (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2021)
This study entitled "The Effect of Current Ratio and Disclosure of Corporate Social Responsibility on Earning Response Coefficient in Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX)". The purpose of this study is to explain how much influence the Current Ratio and disclosure of Corporate Social Responsibility have. simultaneously on the Earning Response Coefficient of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. This research is a quantitative descriptive study with data analysis techniques used, namely multiple linear regression and hypothesis testing (t test and f test). In this study, the sampling technique used was purposive sampling. The data collection technique in this study is documentation, by collecting data on financial statements and annual reports of companies listed on the Indonesia Stock Exchange in 2018-2020.  The results of the partial test (t test) show that the variable Current Ratio has no effect on the Earning Response Coefficient. This is indicated by tcount t table (0.780 1.984). Meanwhile, the CSR Disclosure variable has no effect on the Earning Response Coefficient. This is indicated by the value of tcountttable (-1.551.994). While the results of the simultaneous test (f test) of the two independent variables on the dependent variable show that the acquisition of the value of Fcount Ftable (0.309 3.10), meaning that the Current Ratio (X1) and CSR Disclosure (X2) simultaneously have no significant effect on Earning Response. Coefficient on food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020.